DEVELOPMENT OF MARKETING STRATEGY IN OFFICE STATIONERY COMPANIES OF MENTARI PRIMA - Dewi, Rosalinda Septian; Tanuwijaya, Haryanto; Candraningrat, Candraningrat; Wibowo, Januar (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this article is to explain the business development strategy of a stationary company. The problems that occurred in this company occurred during the Covid-19 pandemic which resulted in a significant decrease in revenue for the company. opportunities and threats facing the company. In addition, it also implements a marketing strategy of segmentation, targeting, and positioning (STP) as well as the 4P marketing mix, namely product, price, promotion, and place. The results of this study indicate that the SWOT analysis, as well as the STP strategy and the 4P Marketing mix, have succeeded in helping the company increase revenue which has now increased by 11%.